The Role of the Board of Commissioners: Determinants in Predicting Bankruptcy Financing Company - Nanang Sugianto Y. K.; Setyani Dwi Lestari (International Journal of Organizational Business Excellence, 2021)
The research aims to determine the role of the board of commissioners in moderating the determinants in predicting the bankruptcy of finance companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The research uses secondary data where the population are all financial companies listed on the Indonesia Stock Exchange for the 2015-2019 period with total of 16 companies. The purposive sampling method is used to collect the data and with certain criteria, 13 companies are selected. The research model uses logit data regression where the dependent variable is a dummy variable, and there is the role of the board of commissioners as a moderating variable. The results show that profitability, liquidity, and solvency has an effect on bankruptcy prediction, risk management has no effect on bankruptcy prediction. The role of the board of commissioners does not moderate the effect of profitability on bankruptcy prediction as well as risk management on bankruptcy prediction